Pengaruh Tenaga Kerja dan Teknologi terhadap Pendapatan melalui Modal sebagai Variabel Intervening UMKM Coffee Shop di Kota Medan - Adhani, Nadia; Ruslan, Dede; Sari, Raina Linda (Masyarakat Ekonomi Syariah Bogor, 2024)
A business that is growing rapidly in the city of Medan is the emergence of coffee shops. Coffee shop visitors do more than just taste coffee; they also use the space for casual gatherings. It is hoped that the coffee shop business in Medan City will have a positive impact on the development of the city, especially in the economic and tourism sectors. The coffee shop business has the potential to increase community income, employment, tourism and coffee production in the city of Medan. The current emergence of coffee shops cannot be separated from the influence of the big city lifestyle which offers lots of fun for entertainment seekers and has become a favorite